2017
DOI: 10.1007/s11356-017-8853-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of normal and dusty day impacts on fractional exhaled nitric oxide and lung function in healthy children in Ahvaz, Iran

Abstract: Children are the vulnerable group at risk of adverse health effects related to air pollution due to dust storm in Ahvaz. The purpose of this study was to compare the values of fractional exhaled nitric oxide (FENO) and lung functions as parameters of adverse health effects of particulate matter (PM) in dusty and normal (non-dusty) days in elementary schoolchildren. The study was conducted among elementary school students in Ahvaz. The healthy elementary schoolchildren (N = 105) were selected from different dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 43 publications
2
14
0
2
Order By: Relevance
“…Few studies have focused on the correlation between FeNO and PM [38]. Most of the previous studies were small cases or were limited to children [39]. In addition, most of the studies were conducted on asthma patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on the correlation between FeNO and PM [38]. Most of the previous studies were small cases or were limited to children [39]. In addition, most of the studies were conducted on asthma patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been carried out in many regions of the world, including southern Europe (Díaz et al, 2012;Faustini et al, 2015;Karanasiou et al, 2012;Mallone et al, 2011;Middleton et al, 2008;Neophytou et al, 2013;Perez et al, 2008;Reyes et al, 2014;Stafoggia et al, 2016;Tobías et al, 2011;Trianti et al, 2017), east Asia (Chiu et al, 2008;Higashi et al, 2014;Kanatani et al, 2010;Kurai et al, 2017;Lee et al, 2008;Lee, 2013Lee, , 2014Nakamura et al, 2016;Nakao et al, 2018;Watanabe et al, 2015Watanabe et al, , 2016Yoo et al, 2008), the Middle East (Al-Taiar & Thalib, 2014;Khaniabadi et al, 2017;Neisi et al, 2017;Thalib & Al-Taiar, 2012;Vodonos et al, 2014Vodonos et al, , 2015, the Caribbean (Cadelis et al, 2014;Gyan et al, 2005;Prospero et al, 2008), and Australia (Barnett et al, 2012;Johnston et al, 2011;Merrifield et al, 2013;Rutherford et al, 1999). However, despite high dust activity in many U.S. states, the United States has lagged behind other regions in the study of dust storms and their health effects.…”
Section: 1029/2020gh000260mentioning
confidence: 99%
“…A Swedish study assessed children biweekly over two months and found that short-term changes in coarse PM were associated with significant increases in FeNO, even after accounting for other ambient air pollutants (Carlsen et al 2016). Among Iranian children, researchers found that, compared to normal days, dusty days were related to significant increases in FeNO and decreases in lung function (Neisi et al 2017). These studies provide evidence of the acute health effects of wind-blown dust exposures among children, which, with repeated insults, have the potential to influence respiratory health over time.…”
Section: A Drying Sea and The Next Generation: Effects Of Wind-blown mentioning
confidence: 99%